Utilization of the Folk Story “Marsikam” as History Learning Material to Develop the Values of Unity and Cooperation among Students - Ihut Marasi Pakpahan; Hendra; Ridwin Purba; Asne Surbakti; Resmi (CV. Creative Tugu Pena, 2025)
This research aims to examine the utilization of the